2004
DOI: 10.1128/iai.72.10.6132-6138.2004
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by Neisseria meningitidis

Abstract: Biofilm formation by the human pathogen Neisseria meningitidis was analyzed. Biofilm-forming meningococcal strains were identified and quantitated by crystal violet staining. Laser scanning confocal microscopy of the meningococcal biofilm revealed variable layers up to 90 m in thickness. A total of 39 meningococcal isolates were studied; 23 were nasopharyngeal-carriage isolates, and 16 were invasive-disease isolates. Thirty percent of carriage isolates and 12.5% of invasive-disease isolates formed biofilms pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 47 publications
8
67
1
1
Order By: Relevance
“…This bacterium is the causative agent of bacterial meningitis, and its ability to colonize the human nasopharyngeal mucosal surface is a key aspect of its pathogenicity. Non-biofilm-forming strains of N. meningitidis were encapsulated, and a capsule-transport mutant (ctrA) gained the ability to form a biofilm (89), similar to the phenotype we observed here with P. gingivalis. Also, it was shown that the expression of capsule, as well as pili, is repressed in N. meningitidis upon contact with host epithelial cells, and this down-regulation facilitated attachment (14).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This bacterium is the causative agent of bacterial meningitis, and its ability to colonize the human nasopharyngeal mucosal surface is a key aspect of its pathogenicity. Non-biofilm-forming strains of N. meningitidis were encapsulated, and a capsule-transport mutant (ctrA) gained the ability to form a biofilm (89), similar to the phenotype we observed here with P. gingivalis. Also, it was shown that the expression of capsule, as well as pili, is repressed in N. meningitidis upon contact with host epithelial cells, and this down-regulation facilitated attachment (14).…”
Section: Discussionsupporting
confidence: 56%
“…According to TIGR annotation, the gene is predicted to be involved in the biosynthesis and degradation of surface polysaccharides and LPS, and therefore, the deletion could result in a strain that is defective in LPS synthesis. A defect in LPS synthesis (expression of a truncated LPS structure) has been shown to enhance biofilm formation in Salmonella enterica (60) and in Neisseria meningitidis (89). The altered biofilm phenotype could also be the result of inactivation of genes downstream of PG0106.…”
Section: Discussionmentioning
confidence: 99%
“…8B). Similar structures with N-acetyl-aspartate were described as constituents of the O-antigen polysaccharides of enterobacteria of the genera Providencia and Proteus (31). The NMR data were confirmed by composition analyses that showed the presence of GlcN, FucN, and Asp.…”
Section: Resultssupporting
confidence: 53%
“…These may encase the gonococci within sac-like structures into which a matrix is released. A recent study of biofilms produced by 39 Neisseria meningitidis strains showed that 30% of the carriage isolates and 12.5% of the invasive disease isolates formed biofilms in microtiter wells (25). Generally, the more hydrophobic the surface of the or- ganism, the more likely it was to form a biofilm, and encapsulation inhibited biofilm formation.…”
Section: Discussionmentioning
confidence: 99%